The Impact of Universal Design for Learning on Student Learning Effectiveness in Elementary Schools (Process and Outcomes) - Triana, Hana; Supena, Asep (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to analyze the relationship between the U.S. learning frameworkuniversal Design for Learning terfacing psychology neuroscience to support the D programdiversity Equality Inclusion ythat can meet the needs of each individualstudent. This study uses the literature review method by analyzing journals/articles with an adjusted number of research articles, web pages, videos, books, And various reputable journals in order to obtain valid, reliable, and up-to-date information. The major themes that became the subject of discussion were related to neuroscience links in personalized learning especially Universal Design for LearningÂ Â Â Â ,Â Â Â Â Universal Design for Learning principles in the learning process, and the strategies and methods involved.This study conducts a literature review based on the following research questions; How does neuroscience affect learning Universal Design for Learning? The general goal is to be able to accommodate every student in learning. To do this, the researcher conducted a journal database. Thus, 25 papers were found, and after applying the criteria, 5 were analyzed. The results show that some of the published works have theoretical conceptions, the results conclude that the Universal principles for Design stimulate the nerves of the brain to be involved in the learning process in exploring learning understandings that are applied in all school inclusions.